Tinjauan Hukum Terhadap Konsumen Akibat Iklan yang Menyesatkan dalam Media Online - Nur Aminah Harahap; Hayatul Ismi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
One of the tools that is often used by businesses to market their products is by advertising. Accordingto law number 8 of 1999 concerning consumer protection, promotion is the activity of introducing ordisseminating information on goods and/or services, to attract consumers’ buying interest in goods and/orservices that will and are being traded. In this case the dissemination of information on an item and/orservice can be carried out in the form of advertisements that are displayed in online media. Problems facedby consumers are goods and/or services that are not as expected as advertised. Due to the misleadingadvertising, business actors should be responsible for losses suffered by consumers.This type of research can be classified in the type of normative legal research, reviewing the legalprinciples contained in law number 8 of 1999 concerning consumer protection. Based on its nature thislegal research is descriptive in that it describes and describes all data obtained from the results of literaturestudies relating to the title of legal writing which is clearly and in detail then analyzed to answer theproblems under study.From the results of research and discussion it can be concluded that, first, consumer protection bythe state, namely by making policies that are tangible in the form of legislation, namely law number 8 of1999 concerning consumer protection. In general the state carries out the task of fostering and supervisingthe implementation of consumer protection, including the task of coaching and supervising advertisingactivities. Another form of consumer protection by the state from misleading advertisements can be seen inthe judge’s fair judgment and the application of legal principles and rules accordingly. Secondly, theresponsibility of business actors towards consumers due to misleading advertisements in online media basedon law number 8 of 1999 concerning consumer protection (UUPK) already exists in the UUPK specificallycontained in Article 20 despite the absence of legislation that regulates related details advertising.